Enhanced antibiotic multi‐resistance in nasal and faecal bacteria after agricultural use of streptomycin. (15th November 2012) - Scherer, Alexandre; Vogt, Hans‐Rudolf; Vilei, Edy M.; Frey, Joachim; Perreten, Vincent
Summary Streptomycin is used in arboriculture to control fire blight. Using sheep as a model, multidrug‐resistant bacteria in mammals were found to be selected after the intentional release of streptomycin into the environment. Escherichia coli and Staphylococcus spp. were isolated from the faeces and nasal cavities, respectively, of sheep grazing on a field sprayed with streptomycin at concentrations used in orchards (test group) and on a field without streptomycin (control group). Before the application of streptomycin, the percentage of streptomycin‐resistant E. coli isolates in faeces was 15.8% in the control group and 14.7% in the test group. After the application of streptomycin, the overall number of streptomycin‐resistant E. coli isolates was significantly higher in the test group (39.9%) than in the control group (22.3%). Streptomycin‐resistant Staphylococcus isolates were only detected after the application of streptomycin. Streptomycin resistance was frequently associated with resistance to sulfamethoxazole, ampicillin, tetracycline and chloramphenicol and less frequently to cefotaxime in E. coli, and to tetracycline, fusidic acid and tiamulin in Staphylococcus spp. This study shows that the application of low concentrations of streptomycin on grass, as occurs during the spraying of orchards, selects for multidrug‐resistant nasal and enteric bacterial flora, including extended‐spectrum beta‐lactamase‐producing E. coli.